Abusive supervision and leader–member exchange: An analysis of attitudinal, emotional and behavioral outcomes - Gençay, Oğuz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The study aims to investigate abusive supervision in the broader context of a supervisor-subordinate relationship. Abusive supervision, such as lying and ridiculing, are detrimental to the employees. However, these behaviors occur in a dyadic and exchange-based relationship between the employee and supervisor – as leader-member exchanges. Little research conducted on both leader-member exchange (LMX) and abusive supervision has produced inconclusive results. This thesis proposes that abusive supervision is a negative antecedent of LMX and outcomes may occur through decreased LMX. Online survey-based two-phased data collection was conducted to test the hypotheses of the study. Participants were contracted through e-mailings or social media ads. Time lag was 1 month. Well established surveys were used. The final sample of 268 respondents was analyzed with mediation analysis of LMX between abusive supervision and outcomes. Full mediation was found for emotional exhaustion, perceived organizational support, and supervisor-directed organizational citizenship behavior (OCB). Both direct and indirect effects (partial mediation) were found for organization-directed OCB, interpersonal OCB, and interactional justice. LMX was insignificant with interpersonal counterproductive work behaviors. As a result, the outcomes are partially or fully mediated by LMX. Results suggest while abusive supervision is harmful, LMX (the broader subordinate-supervisor relationship) also is critical to understand abusive supervision’s detrimental outcomes. LMX may emerge as the most significant mediator of abusive supervision with further studies.
Keywords: Leadership.; Executive ability.